2020
DOI: 10.1590/acb351208
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided study of swine anatomy as a tool for urologic surgery research and training

Abstract: Substantive scientific and intellectual contributions to the study, conception and design, critical revision, final approval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…It should be noted that previous studies have indicated that there are no significant age and gender differences in ureteric diameter. 25 Studies have also shown that the anatomy and physiology of the porcine ureter are broadly comparable to the ones of the human ureter, 26 including its tissue structure 27 and urodynamic parameters. 28 For these reasons, the porcine urinary system is often employed in pre-clinical research on ureteric stents.…”
Section: Methodsmentioning
confidence: 94%
“…It should be noted that previous studies have indicated that there are no significant age and gender differences in ureteric diameter. 25 Studies have also shown that the anatomy and physiology of the porcine ureter are broadly comparable to the ones of the human ureter, 26 including its tissue structure 27 and urodynamic parameters. 28 For these reasons, the porcine urinary system is often employed in pre-clinical research on ureteric stents.…”
Section: Methodsmentioning
confidence: 94%
“…With regard to bronchial measurements, we confirmed that the airway geometry of swine is similar to that in humans (Figure 5), consistent with previous studies. 1,3,4,8,11 The length and angle of the right main-stem bronchus were smaller than those of the left bronchus, suggesting that the right bronchi are shorter and steeper than the left main-stem bronchus. Similar findings have been reported in humans.…”
Section: Discussionmentioning
confidence: 99%
“…10 The anatomic and physiologic similarities of various organ systems, such as the respiratory system, between swine and humans, combined with the wide availability of swine, make swine useful options for research. 3,4,11 These benefits are especially true for research on airway stents and tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Топографія та васкуляризація нирок у тварин має важливе клінічне, діагностичне та хірургічне значення (Packialakshmi et al, 2020;Smit et al, 2021). Знання породних та вікових особливостей топографії та васкуляризації нирок у тварин дозволить ветеринарним спеціалістам своєчасно діагностувати захворювання нирок, проводити комплексне лікування з використанням паранефральної блокади, розробити нові методики оперативного втручання з мінімальною травматизацією органа.…”
Section: результати та їх обговоренняunclassified